2019
DOI: 10.3390/w11030554
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Calibration of a Distributed Hydrological Model in a Highly Glacierized Watershed in Central Asia

Abstract: Understanding glacio-hydrological processes is crucial to water resources management, especially under increasing global warming. However, data scarcity makes it challenging to quantify the contribution of glacial melt to streamflow in highly glacierized catchments such as those in the Tienshan Mountains. This study aims to investigate the glacio-hydrological processes in the SaryDjaz-Kumaric River (SDKR) basin in Central Asia by integrating a degree-day glacier melt algorithm into the macro-scale hydrological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Regarding multi‐criteria calibration, Pellicciotti et al (2012) note that using three different objective functions (NSE, R 2 , and logNSE) deteriorates the model performance, best performance is achieved when only NSE is used. Ji et al (2019), in contrast, affirm that using a combination of streamflow measures performs better than using just one. Schaefli and Zehe (2009) tried out a different calibration approach and calibrated in the wavelet domain instead of in the time domain.…”
Section: Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding multi‐criteria calibration, Pellicciotti et al (2012) note that using three different objective functions (NSE, R 2 , and logNSE) deteriorates the model performance, best performance is achieved when only NSE is used. Ji et al (2019), in contrast, affirm that using a combination of streamflow measures performs better than using just one. Schaefli and Zehe (2009) tried out a different calibration approach and calibrated in the wavelet domain instead of in the time domain.…”
Section: Calibrationmentioning
confidence: 99%
“…Temperature‐index models rely on the assumption that net radiation is the largest contributor to melt, and temperature and several components of the energy balance highly correlate (Hock, 2003). A few studies also used the temperature of the preceding day to calculate melt (e.g., Ji et al, 2019). Degree day factors are commonly different for glacier, snow, and firn (e.g., Li et al, 2019), because of the lower albedo of glacier ice compared to snow (Brock, Willis, & Sharp, 2000).…”
Section: Hydrological Processes In Glacierized Catchmentsmentioning
confidence: 99%
“…This is a critical failure, as temperature and precipitation are considered the most crucial factors affecting the process of glacier and snow accumulation and melting . Previous studies have shown that temperature plays a dominant role in the discharge of the Kumaric River Basin (Ji et al, 2019), whereas in the Toxkan River Basin, the discharge is affected by both temperature and precipitation (Duethmann et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The observed discharge data from 2002 to 2011 at two of the hydrological stations were obtained from the Tarim River Basin Management Bureau of Xinjiang Uygur Autonomous Region, China. Along with meteorological data, the spatial data, including digital elevation model (DEM) data, land use, soil data, and glacier and snow distribution data as described in Ji et al (2019), are used as inputs in the two hydrological models.…”
Section: Datasetsmentioning
confidence: 99%
See 1 more Smart Citation